The Role of Landside and Terminal Operational Airport Officers in Supervising Facilities and Infrastructure at I Gusti Ngurah Rai Airport Denpasar Bali - Putra Denis Purnama; Elnia Frisnawati (CV. Rayyan Dwi Bharata, 2023)
Availability of existing and adequate facilities is a benchmark and a requirement for every airport service provider and its manager to be able to meet the needs of prospective passengers using airport services. Several fields participate in managing, maintaining, supervising the flow of passengers and goods as well as controlling terminal and landside operations, namely the AOLT (Airport Operational Landside and Terminal) unit which plays an important role in supervising and supporting the existing facilities and infrastructure at the airport so that it runs according to provisions of PM 178 of 2015 concerning